The Influence of Social Support on Culture Shock among Migrant Students in Makassar City - Muh Wija Hadi Perdana; Basti Tetteng; Muh. Nur Hidayat Nurdin (Polteknik Ilmu Pemasyarakatan, 2023)
Cultural concussion becomes one of the problems experienced by nomads when in a new environment and symptoms can be lowered by the presence of social support. The goal of the study was to find out the effect of social support on cultural concussions. Data retrieval techniques in this study used snowball sampling with the study subjects of 97 students in Makassar City. The data analysis method used is simple regression. The results showed that social support did not contribute a significant influence to cultural concussion (F(1,91) = 0,001, p > 0,980), dengan nilai R2 = 0,000. This study suggests for future researchers to consider things about the research respondents, such as the sampling method, the characteristics of the research respondents, the cultural contrast of the research respondents, and the duration of the respondent's time since being in a new environment.